Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

‘Where all my bad girls at?’: cosmopolitan femininity through racialised appropriations in K-pop - Garza, Joyhanna Yoo (Gender and Language, 2021)
This article examines the polyvalence of racial(ised) representations in K-pop performances. The analysis of K-pop star CL’s (2013) song and video ‘Nappeun gijibae’ (‘The bad girl’) demonstrates how the artist projects an assertive femininity by embodying and localising the Bad Bitch: a sexually agentive figure of womanhood from US hip hop. CL’s use of African American English and conventionalised hip hop tropes helps resignify gijibae, a pejorative Korean term for women. By shifting between decontextualised styles invoking a different time and place, CL is able to build a kind of chronotopic capital that transforms fragmented styles into an empowered cosmopolitan femininity. However, although CL’s performance challenges Korean gendered norms in its use of local linguistic resources, her selective appropriations of US Black and Chicanx cultural signifiers reproduce narrow images of racialised femininities and reify a hierarchy of valuation along lines of gender and race.
Keywords: 2000 à aujourd'hui; K-pop; approches et analyses; appropriation culturelle; asie; chronotope; corps; corée du sud; cours; discipline; féminisme pop; lin2685; linguistique; performance de genre; premier cycle; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques

Le privé est politique… et économique ! Pour une économie politique du travail de gestation pour autrui: - Jouan, Marlène; Clos, Clémence (Nouvelles Questions Féministes, 2021)
Dans le débat public sur la gestation pour autrui (GPA), parler de « travail » pour qualifier ce que font les femmes porteuses est largement perçu comme une façon de cautionner les formes de marchandisation et d’exploitation du corps des femmes à l’œuvre dans les circuits mondialisés de la bioéconomie. Contre cette interprétation qui accompagne la condamnation morale de cette pratique reproductive, en particulier dans sa version « commerciale », l’article développe une défense féministe de la conceptualisation de la GPA comme travail, appuyée sur les études ethnographiques menées auprès des femmes porteuses indiennes et nourrie théoriquement à la fois par le marxisme, par l’éthique du care et par la notion d’intersectionnalité. In fine, l’objectif est de mettre en lumière la fécondité de cette conceptualisation non seulement pour la pleine reconnaissance des femmes porteuses, mais aussi pour le diagnostic critique des divisions du travail qui structurent la société capitaliste.
Number: 2
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; asie; care; corps; cours; discipline; europe; france; inde; inégalités; maternité; premier cycle; privilèges; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Sémi: roman - Shimazaki, Aki (Actes Sud, 2021)
« Après plus de quarante ans de mariage, Tetsuo et Fujiko se sont installés en maison de retraite car Fujiko, atteinte de la maladie d’Alzheimer, requiert une prise en charge particulière. Un matin, au réveil, elle ne reconnaît plus son époux. D’abord en grand désarroi, Tetsuo entreprend finalement de reconquérir celle qui le prend désormais pour un étranger auquel elle se trouve simplement fiancée. »– Site de l'éditeur
Section: 150 pages ; 19 cm.
Keywords: arts; asie; care; cours; discipline; japon; lit2815; premier cycle; roman; régions géographiques; thématiques; écriture des femmes*; études littéraires